Γ‐Aminobutyric acid and oxalic acid contents and angiotensin‐converting enzyme inhibitory activity of spinach juices cofermented with Levilactobacillus brevis GABA100 and other lactic acid bacteria. (26th August 2022) - Kim, Moon Joo; Lim, Taehwan; Kim, Jaecheol; Ji, Geun Eog; Lee, Haeseong; Lee, Kiuk; Kim, Ryun Hee; Hwang, Keum Taek
Summary: This study aimed to develop fermented spinach juice with enhanced γ‐aminobutyric acid (GABA) level and angiotensin‐converting enzyme (ACE) inhibitory activity and reduced oxalic acid level. We cofermented spinach juice with Levilactobacillus brevis GABA100 and oxalic acid‐degrading bacteria ( Lactobacillus gasseri HHuMin D, Lactobacillus sakei RH1114, Lactobacillus acidophilus 19L5, or Limosilactobacillus fermentum BH03). GABA levels were not different among all the fermented juices except for the juice cofermented with L. brevis GABA100 and L . fermentum BH03. Oxalic acid decreased in the cofermented juices. The most increase in ACE inhibitory activity was observed in the juice cofermented with L. brevis GABA100 and L. sakei RH1114. Peptides (IVVGPPPP, PQTETKASVGFKAG and QIIGPVLD) produced during the cofermentation showed a positive correlation with the ACE inhibitory activity of the juice. These results suggest that spinach juice cofermented with L. brevis GABA100 and L. sakei RH1114 may have potential applications for the management of hypertension. Abstract : Spinach juices cofermented with Levilactobacillus brevis GABA100 and other lactic acid bacteria.